Vapor Annealing and Colloid Lithography: An Effective Tool To Control Spatial Resolution of Surface Modification - Miliutina, E; Guselnikova, O; Marchuk, V; Elashnikov, R; Burtsev, V; Postnikov, P; Svorcik, V; Lyutakov, O (Langmuir, 2018)
Colloid lithography represents a simple and efficient method for creation of a large-scale template for subsequent surface patterning, deposition of regular metal nanostructures, or periodical surface structures. However, this method is significantly restricted by its ability to create only a limited number of structures with confined geometry and symmetry features. To overcome this limitation, different techniques, such as plasma treatment or tilting angle metal deposition, have been proposed. In this paper, an alternative method based on the vapor annealing of ordered single polystyrene (PS) microspheres layer, followed by the surface grafting with arenediazonium tosylates is proposed. Application of vapor treatment before surface grafting allows effective control of the area screened by PS microspheres. Pristine and vapor-annealed microsphere arrays on the gold substrate were electrochemically modified using ADTs. Subsequent removal of the PS microsphere mask enabled to prepare well-defined nanostructures with controllable surface features. In particular, prepared periodic arrangements were achieved by the grafting of OFGs to the empty interspaces between nanopore arrays. The process of sample preparation was controlled, and the properties of prepared structures were characterized by various techniques, including atomic force microscopy (AFM), conductive AFM, scanning electron microscopy energy-dispersive X-ray spectrometry, Raman spectroscopy, and voltammetry.